A study assessing patient satisfaction in otolaryngology OPD of a district medical college of West Bengal - Yasmin, Shamima; Panja, Tanmay Kanti; Baur, Baijayanti (International Journal Of Community Medicine And Public Health, 2019)
Background: Patient satisfaction is perhaps is a proxy indicator to measure the success of a hospital. The aim of this study was to evaluate the level of patient satisfaction among patients attending Otorhinolaryngology outpatient department (OPD) of a tertiary care teaching hospital in a district. Methods: Cross-sectional observational study among 230 patients attending Otorhinolaryngology outpatient department (OPD) of a tertiary care teaching hospital in a district using a modified validated Bengali questionnaire. Analysis of results was done by percentage and proportion. Results: Overall satisfaction was above 60% for only 42.6% of patients. Major dissatisfaction was with the registration system. 50.4% were dissatisfied for waiting at the queue of registration counter to get OPD ticket. Other causes of dissatisfaction were infrastructure e.g. non-availability of adequate seating arrangement (39.6%), fans (58.7%), non-availability of drinking water (71.7%). 78.3% were dissatisfied for the available washroom facilities. However 92% were satisfied by attention paid by doctors. Conclusions: The present study was an attempt to assess the level of satisfaction of the patients. It highlights maintaining privacy during history taking examination and improving infrastructure like drinking water and washroom facilities, improving registration system to decrease waiting time can improve patient satisfaction which can be easily done with help of stakeholders.